Geographische Aspekte des internationalen Handels mit gebrauchter Bekleidung.: Perfektes Recycling oder Verlängerung assymetrischer Handelsbeziehungen mit der Dritten Welt am Fallbeispiel Syrien - Hopfinger, Hans (ERDKUNDE, 1985)
Trading in second-hand textiles has developed into an industry of world-wide proportions. Alongside commercial collectors,more and more charitable organizations have begun, since the1960’s, to appeal for donations of second-hand clothing. The study of the West German second-hand clothing market shows that, at present, between one quarter and one third of all private textile waste is passed on for re-use or further processing. An analysis of the sales figures shows that developing countries are becoming more and more important as trade partners. Taking Syria as a case in point, this study investigates the significance of the further utilization in Third World countries of second-hand clothing collected in Europe. At first glance, the importing of these goods seems to be of advantage to the recipients, in so far as the poorest sections of the population can be provided with good clothing, possibly at very reasonable prices. A closer analysis of the conditions within the Syrian market, however, points to disadvantages in foreign trade, which extend to the structure of the domestic economy, and which involve a number of negative side-effects: - An extensive second-hand clothing market endangers the devel opment of an independent textile and clothing industry. - Traditional crafts and trades are faced with considerable disadvan tages when competing with the importation of second-hand clothing. -The second-hand clothing industry creates little employment, most of which is absorbed by the informal urban sector.